PENGARUH KOMBINASI MAGGOT DENGAN PAKAN KOMERSIL TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Supardan Adam Faisal Al Qausar; Mulyana; Dudi Lesmana (JURNAL MINA SAINS, 2023)
Feed that has a high nutritional content can increase fish growth. One of the natural feeds that can be used is maggot which can be given to fish and can be cultivated by humans so that its availability is always continuous. This research aims to find out the combination of maggot feed with commercial feed as an effort to reduce feed costs in aquaculture activities. This research was conducted in March November 2022 with a trial period of 28 days on May 9 June 9, 2022. This study used a completely randomized design with 4 treatments (40% maggot + 60% commercial feed, 50% maggot + 50% commercial feed, maggot 60% + 40% commercial feed, and Control) and 3 replications. The fish used were Nile Tilapia measuring 4.00 g obtained from the Bayongbong Fisheries Technical Implementation Unit and then randomly stocked into 12 containers. The test parameters included length growth, weight growth, specific weight growth rate, feed efficiency, and survival rate. The results showed that giving maggot combined with commercial feed had a significant effect on the length growth, weight growth, and specific weight growth rate (P<0.05). The best growth was found in treatment of 50% maggot + 50% commercial feed (length growth 3.500 ± 0.100 cm, weight growth 4.400 ± 0.111 g, and specific weight growth rate 3.780 ± 0.017%/day). The combination of maggot and commercial feed had no significant effect (P>0.05) on the survival rate and feed efficiency of Nile Tilapia.